Pobreza, suporte social e sintomas depressivos em pessoas idosas residentes na comunidade e cadastradas em unidades de saúde da família. - Didoné, Letícia Souza (Universidade Federal de São Carlos, 2024)
Poverty is a condition of precariousness that affects various aspects of life, and a significant portion of the elderly population is in this situation, which makes them increasingly vulnerable. The objective of this research was to compare age, sex, education, nutrition, frailty, mood, and social support among older adults residing in areas of high social vulnerability, according to poverty conditions. The study adopted a descriptive, exploratory, and cross-sectional design, with a quantitative approach. It was derived from a longitudinal study called "Monitoring Tool for Frailty Levels in Elderly People Attended in Primary Health Care", and data collection took place from March to August 2018. A total of 238 elderly individuals were interviewed, with inclusion criteria based on age (60 years or older), residence in the Cidade Aracy neighborhood, and participation in previous data collections. The instruments used included sociodemographic questionnaires and assessments of depressive symptoms, nutrition, frailty, and social support. Data analysis was conducted using SPSS and Excel statistical software. Of the 238 elderly individuals interviewed, 174 provided information about income. Among these, 82% were not in poverty, while 18% were. The results indicated that elderly individuals in poverty tend to present more depressive symptoms and lower social support. Factors such as low education, inadequate nutritional status, and physical frailty were associated with a higher likelihood of poverty. It was also found that poverty is a risk factor for the development of depressive symptoms. Social support, especially formal support, played a crucial role in mitigating the effects of poverty. In conclusion, there is an urgent need for public policies that address the vulnerability of the elderly population, both at the local level and in broader regions, to mitigate the effects of poverty and ensure a dignified quality of life for this population. Additionally, there is a need for the development of theories and policies specifically aimed at the reality of the elderly in Latin America.
Poverty, social support, and depressive symptoms among older adults registered in a health care
Keywords: Idosos; Pobreza; Vulnerabilidade Social; Sintomas Depressivos; CIENCIAS DA SAUDE::ENFERMAGEM; 1. Erradicação da Pobreza; 3. Saúde e Bem-Estar; 10. Redução das Desigualdades